2020
DOI: 10.18832/kp2020.66.224
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of sensory evaluation and an electronic nose assay in the assessment of aroma in dry hopped beers

Abstract: The aim of this work was to compare sensory evaluation and electronic nose technology used to assess aromas in dry hopped beers. An electronic nose based on gas chromatography was used for the first time. Hops varieties Amarillo, Cascade, Chinook, Kazbek and Mandarina Bavaria were used for the production of dry hopped beers and the Sladek variety was used for the control sample. The basic characteristics of the beers were determined, and the sensory evaluation performed by selected assessors was compared to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…It has also been a significant source of research, with studies varying from understanding its raw materials, such as malt [2] or hops [3][4][5], to investigating its impact on health [6]. Numerous studies have also investigated beer flavor chemistry, stability and sensory properties [1,[7][8][9][10]. Beer perception is undoubtedly influenced by its chemical composition [11][12][13], but also by cultural factors [14,15] or the level of expertise of the taster [16].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been a significant source of research, with studies varying from understanding its raw materials, such as malt [2] or hops [3][4][5], to investigating its impact on health [6]. Numerous studies have also investigated beer flavor chemistry, stability and sensory properties [1,[7][8][9][10]. Beer perception is undoubtedly influenced by its chemical composition [11][12][13], but also by cultural factors [14,15] or the level of expertise of the taster [16].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are several possible analytes responsible for these identified grapefruit and orange aromas, cis-geraniol (orange, citrus) stands out as one analyte that was only measured in the Sultana-hopped beer and is described in the literature to match this aroma well [19]. Previous publications have highlighted the grapefruit notes in other hop varieties including Kazbek and Chinook, both of which have cis-geraniol as a dominant aromatic compound [8]. Notably, despite the large overall concentration (see Figure 3) of monoterpenes and sesquiterpenes with woody, spicy aromas, these options were not selected by the sensory panelists.…”
Section: Sensory Analysismentioning
confidence: 99%
“…Previous work has shown that the choice of hop variety as well as the method of hop addition are of great importance to the quality of the final product [4][5][6]. Several recent publications have also compared the organoleptic qualities resulting from specific hop varieties and dry hopping methods [7][8][9][10]. However, few previous studies have surveyed the chemical and sensory attributes of Azacca- [11,12], Idaho-7-, and Sultana-hopped beers.…”
Section: Introductionmentioning
confidence: 99%